2014
DOI: 10.1007/s10620-014-3363-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment with Tenofovir in Asian-American Chronic Hepatitis B Patients Is Associated with Abnormal Renal Phosphate Handling

Abstract: Chronic hepatitis B patients treated with ≥18 months of TDF experienced an increased risk of proximal tubular dysfunction. TDF did not increase the risk of osteoporosis. Longitudinal studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 30 publications
0
54
0
4
Order By: Relevance
“…Sebbene negli studi clinici randomizzati, controllati, in pazienti selezionati con epatite cronica B, il trattamento con TDF si sia dimostrato ben tollerato e senza segnalazioni di tossicità renale clinicamente significativa, l'esperienza clinica real life ha riportato casi di compromissione della funzione renale fino all'insufficienza renale e alla sindrome di Fanconi [6,7,[10][11][12][13][14][15][16][17][18][19][32][33][34][35][36][37][38][39]. Spesso i fattori di rischio per un peggioramento della funzione renale sono l'età avanzata, l'ipertensione arteriosa e una preesistente riduzione del filtrato glomerulare.…”
Section: Discussioneunclassified
See 1 more Smart Citation
“…Sebbene negli studi clinici randomizzati, controllati, in pazienti selezionati con epatite cronica B, il trattamento con TDF si sia dimostrato ben tollerato e senza segnalazioni di tossicità renale clinicamente significativa, l'esperienza clinica real life ha riportato casi di compromissione della funzione renale fino all'insufficienza renale e alla sindrome di Fanconi [6,7,[10][11][12][13][14][15][16][17][18][19][32][33][34][35][36][37][38][39]. Spesso i fattori di rischio per un peggioramento della funzione renale sono l'età avanzata, l'ipertensione arteriosa e una preesistente riduzione del filtrato glomerulare.…”
Section: Discussioneunclassified
“…Tra i NUC approvati, entecavir (ETV) e tenofovir disoproxil fumarato (TDF) sono raccomandati in prima linea nel trattamento dell'epatite cronica B, poiché entrambi sono antivirali potenti e con elevata barriera alla resistenza [1][2][3]. Negli studi registrativi e negli studi clinici a lungo termine, sia ETV che TDF hanno mostrato un profilo di sicurezza favorevole [4][5][6][7][8][9][10][11], anche se recentemente sono stati segnalati nella pratica clinica eventi avversi a livello Efficacia e sicurezza di entecavir dopo switch da tenofovir per comparsa di effetti collaterali renali M. Viganò renale e osseo nei pazienti trattati per lungo tempo con TDF [6,7,[10][11][12][13][14][15][16][17][18][19]. I meccanismi alla base della potenziale tossicità dei NUC sono legati alla loro capacità di inibire la DNA polimerasi ϒ mitocondriale umana quando le concentrazioni intracellulari dei NUC superano una soglia critica [12].…”
Section: Introduzioneunclassified
“…A recent meta-analysis study revealed no significant differences between ETV and TDF treatment in CHB patients in terms of renal safety profiles and hypophosphatemia; however, the short duration of the study limited the power of the conclusions [4][5][6]17]. In contrast to these studies [4][5][6]17], PRTD and impaired phosphate renal tubular reabsorption were seen in 15-48% of CHB patients receiving long-term ADV and TDF therapy as in real world clinical experience [8,10,[18][19][20]. Reversibility of renal dysfunction has been shown in HIV-infected patients after cessation of TDF [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
“…[27,30,31]. This resulted in the tubular maximal reabsorption rate of phosphate to GFR (TmPO 4 /GFR) (plasma PO 4 -([urine phosphate × plasma creatinine]/urine creatinine)) (normal 2.8-4.4 mg/dL) [19].…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…However, nephrotoxicity associated with adefovir and tenofovir (both acyclic nucleotide analogs) is related to mitochondrial toxicity in proximal renal tubular cells which manifests as defective proximal phosphate reabsorption and in some instances full-blown Fanconi syndrome [21]. None of the 26 patients manifested overt proteinuria, glycosuria or hypophosphatemia, but more sensitive methods to measure proximal tubular dysfunction were not used in this study [22].…”
Section: Renal Function Esrd On Hd Normalmentioning
confidence: 99%